Sustainable E-Waste Management Through Industry 5.0: A Cambodian Context - Elango, Dinesh (Lembaga Sembilan Tiga Community, 2025)
Cambodia, like many developing nations, faces an urgent need to address the growing e-waste challenge. With an influx of electronic devices and limited e-waste management infrastructure, the environmental and health implications are significant. A people-oriented and sustainable form of development like Industry 5.0 has the potential to revolutionise the management of e-waste. In this paper, the authors focus on the applicability of principles of Industry 5.0, namely the use of collaborative robots, Internet of Things (IoT) and blockchain, for the sustainable management of e-waste in Cambodia. Using data from secondary sources, this study analyses the existing practices of e-waste management in Cambodia, establishes certain deficiencies and proposes Industry 5.0 solutions that would help prevent environmental damage, practice sustainable waste management, and enhance recycling practices. It provides recommendations for policy and regulatory mechanisms to foster better uptake as the overall aim is to support Cambodia’s sustainable development policies.